Activated NK cells reprogram MDSCs via NKG2D-NKG2DL and IFN-γ to modulate antitumor T-cell response after cryo-thermal therapy - Peng Peng; Lisa X Xu; Yue Lou; Shicheng Wang; Junjun Wang; Zelu Zhang; Peishan Du; Jiamin Zheng (Journal for ImmunoTherapy of Cancer)
Background Myeloid‐derived suppressor cells (MDSCs) can potently inhibit T-cell activity, promote growth and metastasis of tumor and contribute to resistance to immunotherapy. Targeting MDSCs to alleviate their protumor functions and immunosuppressive activities is intimately associated with cancer immunotherapy. Natural killer (NK) cells can engage in crosstalk with multiple myeloid cells to alter adaptive immune responses, triggering T-cell immunity. However, whether the NK-cell-MDSC interaction can modulate the T-cell immune response requires further study. Cryo-thermal therapy could induce the maturation of MDSCs by creating an acute inflammatory environment to elicit a CD4+ Th1-dominant immune response, but the mechanism regulating this process remains unclear.Methods NK cells were depleted and NKG2D was blocked with monoclonal antibodies in vivo. MDSCs, NK cells and T cells were assessed by flow cytometry and isolated by magnetic-activated cell sorting (MACS). MDSCs and NK cells were cocultured with T cells to determine their immunological function. The transcriptional profiles of MDSCs were measured by qRT-PCR and RNA-sequencing. Isolated NK cells and MDSCs by MACS were cocultured to study the viability and maturation of MDSCs regulated by NK cells. TIMER was used to comprehensively examine the immunological, clinical, and genomic features of tumors.Results NK-cell activation after cryo-thermal therapy decreased MDSC accumulation and reprogrammed immunosuppressive MDSCs toward a mature phenotype to promote T cell antitumor immunity. Furthermore, we discovered that NK cells could kill MDSCs via the NKG2D-NKG2DL axis and promote MDSC maturation by interferon gamma (IFN-γ) in response to NKG2D. In addition, CD4+ Th1-dominant antitumor immune response was dependent on NKG2D, which promoted the major histocompatibility complex Ⅱ pathway of MDSCs. High activated NK-cell infiltration and NKG2D level in tumors were positively correlated with better clinical outcomes.Conclusions Cryo-thermal therapy induces effective CD4+ Th1-dominant antitumor immunity by activating NK cells to reprogram MDSCs, providing a promising therapeutic strategy for cancer immunotherapy.